Association of Regulatory Factor X 6 gene (rs339331) polymorphism with Prostate Cancer: A case-control study from South India - Daram, Swarnalatha; Poornima, Subhadra; Zubeda, Syeda; P, Akhilesh; V, Ayyala; B, Srinadh; P, Shailaja; A, Sandhya; D, Ramakrishna; Hasan, Q (International Journal of Scientific Research in Biological Sciences, 2019)
Prostate Cancer (PCA) is a heterogeneous disease which exhibits clinical variability, morphological differences and molecular marker diversity. Currently, Prostate specific antigen (PSA) evaluation is the only clinically relevant non-invasive marker for PCA screening. A number of genome wide association studies (GWAS) have identified many susceptibility markers for PCA, one of which is a single nucleotide polymorphism (SNP) rs339331, in Regulatory Factor X 6 (RFX6) gene. The present study evaluated this polymorphism g.16677T>C of RFX6 gene, in PCA, benign prostate hyperplasia (BPH) and controls by PCR using specifically designed primers, followed by restriction digestion. Results show that the frequency of ‘C’ allele is 0.74 in PCA and 0.20 in BPH, which is lower than the frequency in controls, which is 0.35. The ‘C’ allele of RFX6 genotype is significantly associated with PCA (P<0.05). This is the first case-control study from India which shows an association of ‘C’ allele of RFX6 gene g.16677T>C polymorphism with high risk of developing PCA and a potential to use it as a biomarker for identifying men at risk of developing PCA.